2016
DOI: 10.1016/j.amjmed.2015.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Caprini Score for Risk Assessment of Venous Thromboembolism in Hospitalized Medical Patients

Abstract: Background-The optimal approach to assess risk of venous thromboembolism (VTE) in hospitalized medical patients is unknown. We examined how well the Caprini risk assessment model (RAM) predicts VTE in hospitalized medical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 20 publications
4
103
0
1
Order By: Relevance
“…The literature search produced 415 articles on December 17, 2017 (Figure ). After reviewing titles and abstracts, 12 RAMs from 11 developers were obtained to validate; the Padua prediction score, the electronic alert system by Kucher, the electronic alert system by Lecumberri, the NICE guideline, the PRETEMED guideline, the 4‐factor and 7‐factor predicted IMPROVE models, the Geneva risk score, model 2 as published by Zakai et al, the Intermountain risk score, the NAVAL score, and the Caprini risk assessment score . Almost all scores include the presence of active cancer and a previous venous thrombosis as predictors whereas, for example, predictors like ischemic stroke, lower‐limb paralysis or recent travel are included in only three RAMs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature search produced 415 articles on December 17, 2017 (Figure ). After reviewing titles and abstracts, 12 RAMs from 11 developers were obtained to validate; the Padua prediction score, the electronic alert system by Kucher, the electronic alert system by Lecumberri, the NICE guideline, the PRETEMED guideline, the 4‐factor and 7‐factor predicted IMPROVE models, the Geneva risk score, model 2 as published by Zakai et al, the Intermountain risk score, the NAVAL score, and the Caprini risk assessment score . Almost all scores include the presence of active cancer and a previous venous thrombosis as predictors whereas, for example, predictors like ischemic stroke, lower‐limb paralysis or recent travel are included in only three RAMs.…”
Section: Resultsmentioning
confidence: 99%
“…Patients hospitalized for acute medical illness have an eightfold increased risk of venous thrombosis as opposed to the general population . As routine pharmacological thromboprophylaxis for all patients is not recommended due to the associated bleeding risk, risk assessment models (RAMs) have been developed to identify high‐risk patients . International guidelines recommend to prescribe thromboprophylaxis in selected high‐risk medical patients by use of these models…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To help stratify the risk of VTE in hospitalized patients, several RAMs have been suggested . Recently, the Caprini RAM and Padua prediction score have been used to evaluate the risk of VTE clinically and are adopted in “Antithrombotic therapy and prevention of thrombosis, 9th Ed: American college of chest physicians evidence‐based clinical practice guidelines.” The Caprini RAM, which was updated as a relatively mature model in 2010 from its first report in 1980, is configured with a total of 39 individual risk factors of VTE for valid assessment; thus, this RAM was adopted for VTE evaluation in many clinical studies except those on thrombosis involved in IBD . The Padua prediction score was based on the KucherÕs model, with slight modifications for which international guidelines strongly recommended thromboprophylaxis .…”
Section: Discussionmentioning
confidence: 99%
“…19 The Caprini RAM, which was updated as a relatively mature model in 2010 from its first report in 1980, is configured with a total of 39 individual risk factors of VTE for valid assessment; thus, this RAM was adopted for VTE evaluation in many clinical studies except those on thrombosis involved in IBD. [18][19][20][21] The Padua prediction score was based on the KucherÕs model, with slight modifications for which international guidelines strongly recommended thromboprophylaxis. 8 In this study, both RAMs were not found to be significantly associated with the occurrence of VTE by multivariate analysis; thus, these scoring systems were determined to not be useful in patients with IBD who needed hospitalization.…”
Section: Discussionmentioning
confidence: 99%